Perspektif Integrasi Ilmu Terhadap Isu Menentukan Awal Waktu Solat Subuh: The Knowledge Integration Perspective on the Issue of Determining the Time for the Beginning of Fajr Prayer - Abdul Niri, Mohammaddin; Abdul Wahab, Raihana; Mohd Nawawi, Mohd Saiful Anwar; Nayan, Abdul Razak (Jurnal Fiqh, 2021)
The knowledge integration perspective between Shariah and astronomy is structured as the framework to study the issue of determining the time for the beginning of Fajr prayer. As such, the dawn sky observation was conducted at Pantai Bak-bak, Kudat, Sabah using the SQM-LU instrument. The sun’s altitude then was obtained and the appropriate value to indicate both the dawn of ṣādiq at the observation site at that time and the beginning of fajr prayer time is -20.174° ± 0.170°. As a reflection from the knowledge integration perspective, the value is not strong enough as it was obtained only from the graph analysis with no data recorded from the naked-eye observation and the DSLR camera due to the local sky conditions and cloudy horizon. The best value of observation can be considered as a result of the knowledge integration between methods in Shariah and astronomy, especially with the combination of the naked-eye observation as the foundation and then strengthen with the astronomical approach through mathematical calculation and aided-eye observation in the field.